APLIKASI ARTIFICIAL NEURAL NETWORK (ANN) UNTUK MEMPREDIKSI PERILAKU LENTUR PROFIL KANAL (C) FEROSEMEN - Mochammad Afifuddin; Rudiansyah Putra; Andika Akbar (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2013)
Abstract: Objective of this study to predict the flexural behavior of channel profiles (C) Ferosemen by using Artificial Neural Network (ANN). In modeling the effect of different variables is high-profile, number of layers wiremesh, and the amount of reinforcement appeal. The model derived from laboratory test data for 9 pieces of specimen testing that has been done by previous researchers. Steps being taken on the application of ANN there are three stages, namely training, validation, and forecasting. In training randomly selected 7 data for training, and the remaining 2 data selected for validation. Having ascertained the results of training and validation have been getting lessons well, followed by forecasting (predicting). Taken 9 for forecasting new data that has been modified high-profile, number of layers wiremesh, and the amount of tensile reinforcement. From the results obtained values forecasting greatest moments occurred in a high profile 350 mm, 3 layers wiremesh, and 4 rod tensile reinforcement, while the value of the moment of the smallest and the largest value of the deflection occurs in the high profile 150 mm, 3 layers wiremesh, and 2 tensile reinforcement , while the value of the smallest deflection occurs in the high profile 250 mm, 4 layers, wiremesh, and 3 tensile reinforcement. In secondary data, the value of the moment and deflection between ANN modeling (training and validation) compared with laboratory data had an average percentage of 101.81% and 97.45%, while the value of the moment and deflection between theoretical calculations compared with ANN modeling (training and validation) had an average percentage of 80.73% and 58.44%. In the new data, the value of the moment and deflection between theoretical calculations compared with ANN modeling (forecasting) has an average percentage of 78.12% and 60.95%.Keywords : Canal profile (C), ferrocement, Artificial Neural Network, backpropagation.Abstrak: Penelitian ini bertujuan untuk memprediksi perilaku lentur profil kanal (C) Ferosemen dengan menggunakan Artificial Neural Network (ANN). Dalam permodelan yang menjadi variabel adalah pengaruh perbedaan tinggi profil, jumlah lapis wiremesh, dan jumlah tulangan tariknya. Model diambil dari data hasil uji laboratorium terhadap 9 buah benda uji yang telah dilakukan pengujiannya oleh peneliti sebelumnya. Tahapan yang dilakukan pada aplikasi ANN ada tiga tahap, yaitu training, validasi, dan forecasting. Pada training dipilih 7 data secara acak untuk dilatih, dan 2 data sisanya dipilih untuk validasi. Setelah dipastikan hasil training dan validasi telah mendapatkan pembelajaran dengan baik, dilanjutkan dengan forecasting (memprediksi). Diambil 9 data baru untuk forecasting yang telah diubah tinggi profil, jumlah lapis wiremesh, dan jumlah tulangan tarik. Dari hasil forecasting diperoleh nilai momen terbesar terjadi pada profil dengan tinggi 350 mm, 3 lapis wiremesh, dan 4 batang tulangan tarik, sedangkan nilai momen terkecil dan nilai lendutan terbesar terjadi pada profil dengan tinggi 150 mm, 3 lapis wiremesh, dan 2 buah tulangan tarik, sedangkan nilai lendutan terkecil terjadi pada profil dengan tinggi 250 mm, 4 lapis wiremesh, dan 3 buah tulangan tarik. Pada data sekunder, nilai momen dan lendutan antara permodelan ANN (training dan validasi) dibandingkan dengan data laboratorium memiliki persentase rata–rata sebesar 101,81% dan 97,45%, sedangkan nilai momen dan lendutan antara perhitungan teoritis dibandingkan dengan permodelan ANN (training dan validasi) memiliki persentase rata–rata sebesar 80,73% dan 58,44%. Pada data baru, nilai momen dan lendutan antara perhitungan teoritis dibandingkan dengan permodelan ANN (forecasting) memiliki persentase rata–rata sebesar 78,12% dan 60,95%.Kata kunci : Profil Kanal (C), ferosemen, Artificial Neural Network, Backpropagation.